Measuring prescription opioid misuse and its consequences. Issue 4 (8th March 2021) - Dart, Richard C.; Iwanicki, Janetta L.; Black, Joshua C.; Olsen, Heather A.; Severtson, Stevan G.
Abstract : Aims: Prescription drug misuse in the USA increased during the 1990s to 2010. The epidemic stimulated the need new analytical strategies and techniques to understand the medications involved, user characteristics and other factors needed to address the epidemic. Methods: A strategy of mosaic surveillance has evolved. Using real world evidence, the goal is to paint a more complete profile of a drug's real world misuse using triangulation—integrating results from multiple sources, where each approach has unrelated sources of bias. Results: Research findings have been remarkably consistent across multiple data sources. The most commonly misused opioid medications: hydrocodone = oxycodone > methadone = buprenorphine = tramadol = fentanyl (prescription form) > morphine > hydromorphone = oxymorphone > tapentadol. This rank order is similar to the number of prescriptions dispensed for each product in the USA. In the USA, prescription opioid misuse started to decrease about 2011. Typically, multiple drugs are misused together, particularly in lethal cases. Immediate release formulations are more commonly misused than extended release formulations. The introduction of tamper resistant formulations to resist crushing were followed by a decrease in misuse of those products. Conclusions: The rapid expansion of opioid prescribing was accompanied by increasing misuse and mortality. Interventions such as prescription drug monitoring programmes, increased law enforcement and abuse deterrent formulations have been followed by decreases in misuse of most opioid analgesics.